Changes in sport-related concussion and traumatic brain injury in New Zealand during the first two years of the COVID-19 pandemic - Lystad, R. P. (Journal of Science and Medicine in Sport, 2023)
Objectives: To quantify changes in sport-related concussion and traumatic brain injury claims in New Zealand during the first two years of the COVID-19 pandemic (i.e., 2020 and 2021). Design: Population-based cohort study. Methods: This study included all new sport-related concussion and traumatic brain injury claims that were registered with the Accident Compensation Corporation in New Zealand during 1 January 2010 to 31 December 2021. Annual sport-related concussion and traumatic brain injury claim rates per 100,000 population from 2010 to 2019 were used to fit autoregressive integrated moving average models, from which forecast estimates with 95% prediction intervals for 2020 and 2021 were derived and compared against corresponding observed values to obtain estimates of absolute and relative forecast errors. Results: Sport-related concussion and traumatic brain injury claim rates were 30?% and 10?% lower than forecasted in 2020 and 2021, respectively, equating to an estimated total of 2410 fewer sport-related concussion and traumatic brain injury claims during the two-year period. Conclusions: There was a large reduction in sport-related concussion and traumatic brain injury claims in New Zealand during the first two years of the COVID-19 pandemic. These findings highlight the need for future epidemiological studies examining temporal trends of sport-related concussion and traumatic brain injury to account for the impact of the COVID-19 pandemic.